Forever young? Marx’s Critique of political economy after 200 years - Bellofiore, Riccardo (PSL Quarterly Review, 2019)
This article suggests a reconstruction of Marx’s Critique of political economy as a macro-monetary theory of capitalist production. The first part of what follows will provide a sort of methodological introduction to Das Kapital. I am questioning the meaning of critique versus criticism, the distinction between fetish-character and fetishism, the role of dialectics, and the difference between reading, interpreting and reconstructing. I will focus especially on volume I. At the centre of the discussion are: the multiple meanings of abstract labour and socialization, the role of money as a commodity for the labour theory of value, the ‘method of comparison’ in grounding valorisation (the emergence of gross profits) as the constitution of capital from class struggle in production, the unity of absolute and relative surplus value extraction, the key notion of Technologie in the real subsumption of labour to capital, the law of the tendential fall in relative wage, Marx’s two notions of competition, and the macro-monetary class perspective in capitalist reproduction crucial to Capital, volume I. Some considerations are devoted to the transformation problem, the so-called “New Interpretation”, and crisis theory. JEL codes: B14, B24, B51 Keywords: Marx, value, money, crisis, macro-monetary theory of capitalist production